Management as an Entrepreneurial Activity: The Internationalization of the Argentine Company Siderca (1960-1996) - Castro, Claudio (2014)
This paper analyzes and explains the process of internationalization of an Argentine company that produces seamless pipes. Siderca initiated its activities during the import substitution phase in Argentina and later achieved international market leadership. The explanation for this breakthrough onto the global stage is to be found in the arrival of a new and young group of middle managers who were promoted from within the corporation. This pattern is consistent with the literature on the role of middle management in the design and implementation of strategic change. The transformations in this company also influenced the rest of the activities of the Techint Group.